Apoyo al área de gestión ambiental de la empresa Triturados Paz De Río del municipio Paz de Rio (2022)
This document is a report on the sup port provided to the environmental management area of the company Triturados Paz de Río in the municipality of Paz de Río in the department of Boyacá during the internship period, where the activities developed under the guidelines established by the compa ny are evidenced. The internship was aimed at obtaining indicators from data provided by the water and energy meters, as well as the quantification of the waste generated in terms of RESPEL and of common origin. The project aims to provide an analysis of t he management carried out by the company in the months of July, August, September and October 2022, in order to study and compare with indicators, the data collected this year and those obtained for the year 2021. Ending this report with the respective ana lysis and interpretation of the results of the research carried out, a series of conclusions and recommendations have been reached aimed at the solution and improvement of the institution where it was possible to carry out this project